2012
DOI: 10.1021/cm301206e
|View full text |Cite
|
Sign up to set email alerts
|

Supported Core/Shell Bimetallic Nanoparticles Synthesis by Atomic Layer Deposition

Abstract: A continuing goal in catalysis research is to engineer the composition and structure of noble metal nanomaterials in order to precisely tune their catalytic activity. Herein, we present proof-of-concept results on the synthesis of supported bimetallic core/shell nanoparticles entirely by atomic layer deposition (ALD). ALD is a novel and scalable method, which can be used to prepare noble-metal catalysts on high surface area support materials. Two properties of ALD of noble metals, namely the Volmer−Weber growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
183
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(184 citation statements)
references
References 33 publications
1
183
0
Order By: Relevance
“…This innovative method is a two-step process that makes use of the island growth during the initial stage of metal ALD in order to deposit the core material and of a selective ALD process to cover these cores with a shell of another metal. We presented and reported this general strategy by synthesizing supported Pt/Pd and Pd/Pt core/shell NPs on metal oxides surfaces [36]. Lu et al recently adopted and extended this method by preparing core/shell NPs with different combinations of noble metals, including Pd, Pt and Ru supported on metal oxides [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This innovative method is a two-step process that makes use of the island growth during the initial stage of metal ALD in order to deposit the core material and of a selective ALD process to cover these cores with a shell of another metal. We presented and reported this general strategy by synthesizing supported Pt/Pd and Pd/Pt core/shell NPs on metal oxides surfaces [36]. Lu et al recently adopted and extended this method by preparing core/shell NPs with different combinations of noble metals, including Pd, Pt and Ru supported on metal oxides [37].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the area selectivity of an ALD process toward specific materials, such as noble metals, can be achieved by tuning the process parameters, e.g. the temperature [40], the pressure [41], the nature of the coreactant or combinations thereof [36,37]. Key for these selective ALD processes of noble metals, such as Pt and Pd, is their catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57] Kessels and coworkers reported that when the O 2 partial pressure decreased to 7.5 mTorr, the growth of Pt on Al 2 O 3 was inhibited. 36 No Pt growth was observed on Al 2 O 3 surface even after 600 cycles. While under such condition, Pt could still initiate its growth on Pd without delay and form core shell structure exclusively.…”
Section: Core Shell Catalytic Structuresmentioning
confidence: 97%
“…The preparation of core shell nanoparticles with three strategies and their applications will be reviewed initially. [34][35][36] Consequently, oxide overcoating catalysts fabricated via selective ALD are discussed. The discontinuous coating structures range from random porous coating to more ordered structures, such as selective deposition on edges sites or facets are highlighted in this section.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 The atomic layer deposition (ALD) method for Pt deposition on CNTs is a dry, gas phase process and possesses several advantages such as good deposition uniformity, feasible ultrafine size, and easy loading control. These characteristics make ALD an ideally suitable method to prepare nanocatalysts with high specific catalytic activity.…”
mentioning
confidence: 99%